2015 Kansas Performance Tests with Sunflower Hybrids - Evans, Patrick (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2017)
Sunflower performance tests were conducted in 2015 by the Kansas Agricultural Experiment Station to provide farmers, extension workers, and private industry with unbiased agronomic information on many of the sunflower hybrids marketed in the state. Tests were financed in part by entry fees from private companies. Companies known to be developing and marketing sunflowers were invited to participate and enter hybrids on a voluntary, fee-entry basis. As a result, not all hybrids grown in the state were included in the tests, and hybrids were not grown uniformly at all locations. Contributors: Patrick Evans, Research Technologist (Senior Author), Colby; Jane Lingenfelser, Assistant Agronomist, Manhattan; Mary Knapp, Kansas State Climatologist, Manhattan; Gary Cramer, Agronomist, Hutchinson; Lonnie Mengarelli, Parsons; Gerald Rohleder, Hays; Alan Schlegel, Agonomist, Tribune.
Keywords: Sunflower hybrids; Yield; Oil percentage; Statistical analysis; Seed size